Biodiversity among Mediterranean durum wheat landraces for the improvement of quality and adaptation - Royo C.; Moragues M.; Moralejo M. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Mediterranean durum wheat landraces are expected to hold the largest genetic variability in the world for this species. Sixty three landraces from 12 Mediterranean countries were used in a study of the genetic diversity existing between genotypes of different geographical origin within the region. The allelic composition for high and low molecular weight glutenin subunits revealed a relatively high genetic diversity, with 42 haplotypes, 20 allele combinations at the HMW-GS loci, and 18 at the LMW-GS. Quality profiles grouped the landraces in two pools, being the South-West Asian landraces different from the ones of other Mediterranean areas. Genetic variability in the population was assessed by means of 8 AFLPs primer combinations and 20 SSR loci. Cluster analysis based on Roger's distance and multi-dimensional scaling suggest landraces from the North and the South of the Mediterranean basin having contrasting genetic structures. Results of three field experiments conducted in Lleida in rainfed environments, where yield ranged from 1.5 to 3.5 t/ha, showed that landraces from the North and the South of the Mediterranean basin had different biomass production and allocation, as well as contrasting yield formation strategies and water use efficiency. Our results fit in the framework of the climatic conditions prevalent in both regions, and may be useful to design breeding strategies to improve the adaptation of durum wheat.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)